1981
DOI: 10.1002/cne.901950207
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of thalamocortical and other synaptic inputs to dendrites of two non‐spiny neurons in a single barrel of mouse SmI cortex

Abstract: A Golgi impregnated, non-spiny multipolar cell whose soma occurred in layer V of the region of mouse SmI cortex containing the posteromedial barrel subfield (PMBSF) (Woolsey and Van der Loos, '70) was gold-toned and deimpregnated (Fairen et al., '77). Two of its dendrites, contained within a single PMBSF barrel, were serial thin-sectioned and then reconstructed in three dimensions. Dendrites of an unimpregnated, non-spiny layer IV bitufted cell, present within the same barrel, were also reconstructed in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 26 publications
3
28
2
Order By: Relevance
“…Comparison of responsive and nonresponsive inhibitory interneurons suggested that, as in the comparison with excitatory neurons above, it was not the intrinsic properties of the interneuron that determined its responsiveness, but most likely the magnitude of the thalamocortical synaptic input it received. The differences in the magnitude of thalamic input onto different inhibitory interneurons are probably the functional correlates of the variability in the numbers and locations of thalamocortical synapses made on them (White and Rock, 1981;White et al, 1984;Keller and White, 1987).…”
Section: Only a Subset Of All Inhibitory Interneurons Are Activated Bmentioning
confidence: 99%
“…Comparison of responsive and nonresponsive inhibitory interneurons suggested that, as in the comparison with excitatory neurons above, it was not the intrinsic properties of the interneuron that determined its responsiveness, but most likely the magnitude of the thalamocortical synaptic input it received. The differences in the magnitude of thalamic input onto different inhibitory interneurons are probably the functional correlates of the variability in the numbers and locations of thalamocortical synapses made on them (White and Rock, 1981;White et al, 1984;Keller and White, 1987).…”
Section: Only a Subset Of All Inhibitory Interneurons Are Activated Bmentioning
confidence: 99%
“…Although a small fraction (ϳ20%) of these thalamic afferents terminate on aspinous, presumably GABAergic interneurons (White and Rock, 1981;White et al, 1984;Benshalom and White, 1986), their main target cells are excitatory spiny neurons in layer 4. Most of these neurons resemble spiny stellate cells, whereas a smaller fraction has been described as star pyramidal cells (Lund, 1984;Ahmed et al, 1994;Hirsch, 1995).…”
Section: Abstract: Barrel Cortex; Layer 4; Spiny Stellate Cell; Starmentioning
confidence: 99%
“…In the rodent whisker system, ascending thalamic input engages neuronal circuits in cortical layer 4 (L4), consisting of excitatory spiny stellate and pyramidal cells as well as aspiny interneurons (White and Rock, 1981;Beierlein et al, 2002Beierlein et al, , 2003Bruno and Simons, 2002) that provide feedforward and feedback inhibition to the local network (Agmon and Connors, 1991;Swadlow and Gusev, 2000;Porter et al, 2001;Swadlow, 2003;Staiger et al, 2004). This functional architecture leads to a precise sequence of excitation followed by inhibition in response to whisker deflection that may serve to sharpen the spike timing of suprathreshold responses and limit the time for integration of excitatory inputs (Pinto et al, 2000(Pinto et al, , 2003Pouille and Scanziani, 2001;Wehr and Zador, 2003;Wilent and Contreras, 2004;Blitz and Regehr, 2005;Mittmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%